RESILIENSI PADA PERUSAHAAN SKALA USAHA KECIL MENENGAH (UKM) - Lenasari, Rekha Puspa; Purbasari, Ratih; Purnomo, Margo (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Resilience in SMEs is explained based on the results of the research that has been done represented by three aspects, first Resilience is more studied with a focus on the theme of Sustaibanilitas in tourism sector SMEs. Second, during the Covid-19 period, traditional retail SMEs were vulnerable to supply chain problems and were dominantly studied in relation to strategies to survive. And third, innovation and sustainability are seen by researchers as key concepts for success in building SME resilience. This research is a qualitative research with systematic literature review method. This research presents a text analysis so that it is expected to bring up the current state of resilience studies in SMEs. Based on the results of text analysis, it is also known that the emerging issues on business resilience in SMEs are still dominated by Covid-19 issues. Empirical gaps that can be followed up in future research include those related to the ability of SMEs to improve their business resilience by adopting post-Covid-19 innovation and sustainability theory. Especially related to changes in supply and demand behavior as described in the introduction.